Gastrointestinal problem among Indian adults: Evidence from longitudinal aging study in India 2017–18 - Dawoodi, Sameer; Dawoodi, Inshiya; Dixit, Priyanka (Frontiers in Public Health, 2022)
Introduction Diseases and illnesses of the gastrointestinal system (GIS) have grown in the last decade due to considerable lifestyle changes. People with gastrointestinal (GI) diseases have a high prevalence of depression, stress, anxiety, and impaired central nervous system functioning. Therefore, this study aims to explore the factors associated with the self-reported gastrointestinal problems among the Indian elderly and to explore the relationship between non-communicable diseases (NCDs), such as hypertension, heart diseases, diabetes, and neurological or psychiatric and gastrointestinal disorder. Methods This study uses data from the Longitudinal Aging Study in India (LASI), a population-based national survey, conducted during 2017–2018 with a representative sample of 72,250 individuals. Descriptive statistics were used to provide the frequency distribution of sociodemographic and economic profiles of adults. Bivariate analysis was used to understand the percentage distribution of adults suffering from gastrointestinal problems by their background characteristics. Binary logistic regression was used to determine the factors associated with gastrointestinal problems. In the binary logistic regression analysis, a systematic model building procedure was adopted. Results The overall prevalence of self-reported gastrointestinal problems was 18%, with significant variations among regions, and it substantially increased with the increasing age of men. Hypertension and neurological problems have significant individual effects on gastrointestinal problems. Prevalence was higher in those who suffered from neurological or psychiatric problems (27%) than in those who suffered from hypertension (22%) and heart disease (23%). Adults from the age group 45–54 (1.11, p < 0.01) and 55–64 (1.09, p < 0.01) years were significantly more likely to have gastrointestinal problems compared with the <44 years age group. Former and current smokers and adults with the habits of chewing tobacco were significantly more likely to report gastrointestinal problems than their counterparts. Moreover, the increasing economic status significantly and positively increased the likelihood of having self-reported gastrointestinal problems among adults. Conclusion Aging-related gastrointestinal problems are physiological or pathological and more prevalent in the elderly population aged 64 years and above. Hence, policies and interventions have to be made age-specific. Gastrointestinal problems among older adults are acquiring greater importance in clinical practices to plan effective treatment, administration of gastrointestinal drugs, the early screening of gastrointestinal diseases. Given the policy focus through Health and Wellness centers for accessible NCD care, it is important that gastro-intestinal illnesses receive more focus and systemic support.